HUBUNGAN KADAR ESTROGEN DENGAN KADAR DEOXYPIRIDINOLIN URIN PADA WANITA MENOPAUSE - Wardhiana, I Putu Gede (journal of internal medicine; Vol. 8, No. 3 September 2007, 2012)
Women in her life will get two land marks, menarche and menopause. Menopause is that point in time when permanent cessation of menstruation occurs following the loss of ovarian activity. Women will loss the protective effect of estrogen, accelerate bone remodeling and get osteoporotic. This study was conducted to evaluate relationship between estrogen level and bone resorption by deoxypyridinoline ekskretion in urine of menopausal women. Cross sectional study was done at Obgyn Department, RS Sanglah Denpasar. Population in this study were women who got cessation their menstruation for 12 months or more, including our inclusion criteria and the worked in this hospital. We performed deoxypyridinoline urine by high performance liquid chromatography (HPLC) method at Klinik Prodia and basal estradiol level (E2) at Laboratorium Graha Tunjung RS Sanglah Denpasar. 52 menopausal women were evaluated, 21.1% with normal estradiol level, and 78.9% low (< 30 pg/ml). We collected 75% normal deoxyyridinoline urine and 25% with high deoxypyridinoline urine level (> 7.5 nmol/L), 1 sample with normal estradiol got high deoxypyridinoline urine level. From 41 sample (78.9%) with low estradiol level, twelve (23.1%) with high deoxypyridinoline have the highest osteoporotic risk in their life. Conclusion: 23,1% sample with low estradiol level and high deoxypyridinoline have the highest osteoporotic risk in their life
Keywords: menopause, estrogen, deoxypyridinoline